Streptococcal M6 protein binds to fucose-containing glycoproteins on cultured human epithelial cells. - Wang, J R (1994)
M6 protein of Streptococcus pyogenes binds directly to HEp-2 cell surfaces and helps to mediate bacterial adhesion. Two epithelial cell receptors for M protein were identified as 97- and 205-kDa glycoproteins. Purified recombinant M6 protein (rM6) showed a dose-dependent and saturable binding to isolated HEp-2 membranes in an enzyme immunoassay. The HEp-2 cell receptors were selectively denatured by pretreatment of isolated membranes at 80 degrees C or with chymotrypsin; binding activity for rM6 was reduced 83 and 80%, respectively. Pretreatment of the HEp-2 membranes with neuraminidase-N-glycosidase, neuraminidase-O-glycosidase, alpha-L-fucosidase, or Ulex lectin caused 33, 42, 73, and 80% reduction of rM6 binding, respectively. Quantitative analysis of HEp-2 cells pretreated with alpha-L-fucosidase showed that the 97- and 205-kDa glycoproteins lost 70 and 62% of their abilities to bind M6 protein and that 33% of the HEp-2 cell's ability to bind whole streptococci was also lost. These results indicated that binding of M6 protein to HEp-2 cell surfaces is highly selective for certain fucose-containing oligosaccharides on these glycoproteins.